A neuropilin-1 antagonist exerts antitumor immunity by inhibiting the suppressive function of intratumoral regulatory T cells - Jung, Keunok; Kim, Jeong Ah; Kim, Ye Jin; Lee, Hyun Woo; Kim, Chul Ho; Haam, Seokjin; Kim, Yong Sung (Cancer Immunology Research, 2020)
Regulatory T cells (Treg) are targeted for cancer immunotherapy because they suppress antitumor immunity. Although the importance of neuropilin-1 (NRP1) in the stability and function of intratumoral Tregs is well-documented, targeting of NRP1þ Tregs for anticancer immunotherapy has not been well explored. Here, we found that an NRP1 antagonist [Fc(AAG)-TPP11], generated by fusion of the NRP1-specific binding peptide TPP11 with the C-terminus of an effector function–deficient immunoglobulin Fc(AAG) variant, inhibits intratumoral NRP1þ Treg function and stability. Fc(AAG)-TPP11 triggered the internalization of NRP1, reducing its surface expression on Tregs and thereby inhibiting the suppressive function of Tregs. In two murine syngeneic tumor models, Fc(AAG)-TPP11 retarded tumor growth, comparable with a Treg-depleting anti–CTLA-4 antibody, without noticeable toxicity. Fc(AAG)-TPP11 inhibited NRP1-dependent Treg function, inducing unstable intratumoral Tregs, with reduced expression of Foxp3 and enhanced production of IFNγ, which subsequently increased the functionality and frequency of intratumoral CD8þ T cells. We also observed selective expression of NRP1 on Tregs isolated from human tumors, but not from the blood of healthy donors and patients with cancer, as well as ex vivo inhibition of intratumoral NRP1þ Treg function by Fc(AAG)-TPP11. Our results suggest that the NRP1 antagonist Fc(AAG)-TPP11 has therapeutic potential for the inhibition of intratumoral NRP1þ Tregs with limited unfavorable effects on peripheral Tregs.
Keywords: Animals; CD8-Positive T-Lymphocytes; Cell Line, Tumor; Colonic Neoplasms; Female; Immunoglobulin Fc Fragments; Immunosuppression; Melanoma; Mice; Mice, Inbred BALB C; Mice, Inbred C57BL; Mice, Nude; Neoplasms, Experimental; Neuropilin-1; Peptide Fragments; Skin Neoplasms; T-Lymphocytes, Regulatory